Rituals, icons, and imaginary: a dialogue between anthropology and psychotherapy - Raffaele Menarini; Domenico Agresta (Forum for Group Psychotherapies and Processes)
This work presents a connection and an interpretation between psychotherapy and anthropology studies considering a common field in the experience of the ritual as a process of transformation and the rituality of the setting. Based on the assumption that the ritual is the set and the setting is the representation of it, in terms of creation and observation of foundation myth, we can observe the complexity inside the therapeutic relation and the function of imaginary, the matrix and myth, as well as reflect on them.